Critical temperature for the components of composite slabs with steel deck under fire for load-bearing rating - Piloto, P.A.G. (2020)
Composite slab made with concrete and steel deck are widely used in building structures. They also include other components, such as steel rebars for positive bending and a steel mesh for negative bending. The fire rating of this type of elements can be determined by standard fire tests, accounting for load (R), Integrity (E) and Insulation (I). This investigation deals with the fire resistance for load (R) and insulation (I), using a numerical model validated with experimental tests. This model considers material and geometric non-linear behaviour, using perfect contact between materials. The 3D finite element mesh uses solids, shells and bars, to model a simple supported composite slab with 3.2m long, 0.65 m wide and total height of 143mm, using a trapezoidal steel deck PRINS PSV73. Different load levels are simulated (live load ranging from 1.0 K/m2 to 21 kN/m2) in addition to the dead load (2.8 kN/m2). The fire resistance is determined according to standards, looking for the maximum displacement or the rate of displacement. The critical temperature of each steel component decreases with the load level. A new proposal is presented for the critical temperature of each steel component.